2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16261
|View full text |Cite
|
Sign up to set email alerts
|

Teaching And Assessment Experiences Of An Undergraduate Mechanical Engineering Design Course

Abstract: Teaching and learning a fundamental core course such as Mechanical Engineering Design (or Machine Design) continues to be fun but a challenging task for many instructors, as well as for students. It certainly helps if an instructor has both hands on and/or professional consulting experience to share their rich and real-life knowledge to keep the students engaged in a classroom and to add value to the course. A typical Machine Design course truly integrates the core concepts taught in Linear Algebra, Statics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Chen et al effectively incorporated PBL in teaching renewable energy courses to engineering technology students, where PBL helped students understand the basic concepts of various types of renewable energy while applying the concepts in design (9). Echempati and Dippery found PBL a promising method to teach a mechanical engineering design course (10). It has been well documented that most students who were exposed to the PBL methodology found it an exciting and rewarding approach, and they were able to produce original and innovative concepts (11).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al effectively incorporated PBL in teaching renewable energy courses to engineering technology students, where PBL helped students understand the basic concepts of various types of renewable energy while applying the concepts in design (9). Echempati and Dippery found PBL a promising method to teach a mechanical engineering design course (10). It has been well documented that most students who were exposed to the PBL methodology found it an exciting and rewarding approach, and they were able to produce original and innovative concepts (11).…”
Section: Literature Reviewmentioning
confidence: 99%
“…9 Echempati and Dippery found PBL a promising method to teach a mechanical engineering design course. 10 It has been well documented that most students who were exposed to the PBL methodology found it an exciting and rewarding approach, and they were able to produce original and innovative concepts (Tsai et al, 2010). 11 Melin et al (2010) showed incorporation of the PBL method into course material can help students achieve a higher level of development in the cognitive domain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PBL has been successfully used to teach higher-level undergraduate and graduate courses in engineering curriculum. Examples include but not limited to courses in structural and materials failure mechanisms [7], renewable energy courses [8], and senior design mechanical courses [9]. 1.…”
Section: Introductionmentioning
confidence: 99%